An efficient route to fabricate fatigue-free P(VDF-TrFE) capacitors with enhanced piezoelectric and ferroelectric properties and excellent thermal stability for sensing and memory applications. Issue 11 (6th March 2017) - Singh, Deepa; Deepak,; Garg, Ashish
Abstract : P(VDF-TrFE), the best known ferroelectric polymer, suffers from a rather low piezoelectric response as well as poor electrical fatigue life, hampering its application potential. Abstract : P(VDF-TrFE), the best known ferroelectric polymer, suffers from a rather low piezoelectric response as well as poor electrical fatigue life, hampering its application potential. Herein, we report the fabrication of fatigue free poly(vinylidenedifluoride-trifluoroethylene) P(VDF-TrFE)-based capacitors with record piezoelectric coefficients and excellent thermal stability. We proposed a cost-effective and simple solution-based process to fabricate P(VDF-TrFE)-based memory capacitors with large polarization (8.9 μC cm −2 ), low voltage operation (15 V), and excellent fatigue endurance with 100% polarization retention up to 10 8 electrical switching cycles. The thin film capacitors fabricated using methyl ethyl ketone (MEK) and dimethyl sulfoxide (DMSO) as co-solvents also show a much higher piezoelectric coefficient ( d 33 = −60 pm V −1 ) than the previously reported capacitors and are also thermally stable up to 380 K, making them ideal candidates for ferro-, piezo-, and pyro-electric applications, even in devices operating above room temperature. The observed results are well supported by first principles calculations, FTIR, XPS, and evaluation of cohesion energy for crystallization by DSC.